2022
DOI: 10.1016/j.biopha.2022.112658
|View full text |Cite
|
Sign up to set email alerts
|

Natural products can be used in therapeutic management of COVID-19: Probable mechanistic insights

Abstract: The unexpected emergence of the new Coronavirus disease (COVID-19) has affected more than three hundred million individuals and resulted in more than five million deaths worldwide. The ongoing pandemic has underscored the urgent need for effective preventive and therapeutic measures to develop anti-viral therapy. The natural compounds possess various pharmaceutical properties and are reported as effective anti-virals. The interest to develop an anti-viral drug against the novel severe acute respiratory syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 195 publications
(223 reference statements)
2
47
0
6
Order By: Relevance
“…The binding site residues which are not involved in forming the hydrogen bond with ligands also show a higher range of distances. Previously, different in silico and in vitro studies reported a similar trend of tightly fitting inhibitors in the binding pocket of SARS-CoV-2 M pro , which confirms our study ( Park et al, 2015 ; Aanouz et al, 2020 ; Bello et al, 2020 ; Chikhale et al, 2020 ; Krupanidhi et al, 2020 ; Kumar et al, 2020 ; Muhammad et al, 2020 ; Tripathi et al, 2020 ; Mitra et al, 2021 ; Varadharajan et al, 2021 ; Ali et al, 2022 ; Linani et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…The binding site residues which are not involved in forming the hydrogen bond with ligands also show a higher range of distances. Previously, different in silico and in vitro studies reported a similar trend of tightly fitting inhibitors in the binding pocket of SARS-CoV-2 M pro , which confirms our study ( Park et al, 2015 ; Aanouz et al, 2020 ; Bello et al, 2020 ; Chikhale et al, 2020 ; Krupanidhi et al, 2020 ; Kumar et al, 2020 ; Muhammad et al, 2020 ; Tripathi et al, 2020 ; Mitra et al, 2021 ; Varadharajan et al, 2021 ; Ali et al, 2022 ; Linani et al, 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…CA might enhance the cytotoxic activities of M1 macrophages and block cancer growth; inhibitory action on TAMs can be induced by its antioxidative action. However, the anticancer action of CA has been the effect of the synergistic actions of diverse mechanisms through which CA performs on proliferation, survival, angiogenesis, and immunomodulation ( 64 66 ). CA competently inhibited the incidence of TAMs and noticeably repressed tumorigenesis in mouse tumor models.…”
Section: Biological Mechanism Of Action Of Caffeic Acidmentioning
confidence: 99%
“…Interestingly, natural compounds and phytoconstituents have also been considered for their anti-viral functions and potential therapeutic effects in the management of COVID-19 ( Nallusamy et al, 2021 ; Ali et al, 2022 ). Among the others, it has been reported that phillyrin could significantly inhibit SARS-CoV-2 replication in vitro ( Ma et al, 2020a ), and it has been shown the ability of reducing the protein expression of NF-kB p65 in vitro as well as the release of pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%